Design, Characterization, and Preparation of New Smart Photoactive Polymers and Their Capacity for Photodynamic Antimicrobial Action in Organic Film - Martin-Trasancos, R; Martin-Trasancos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The photosensitive properties of smart photoactive polymers give them a wide range of potential applications across various fields. This study focuses on designing polymeric systems that incorporate hydrophilic polymers, with the primary goal of adapting these materials for biological applications. Specifically, it aims to contribute to the development of photochromic materials for optical processing, utilizing both molecular and macromolecular components. Additionally, this study evaluates the effectiveness of photoactive polymers in photodynamic therapy (PDT). It details the synthesis and characterization of photoactive copolymers derived from maleic anhydride (MAn) combined with vinyl monomers such as 2-methyl-2-butene (MB) and 1-octadecene (OD), as well as the organic compound 1-(2-hydroxyethyl)-3,3-dimethylindoline-6-nitrobenzopyran (SP). The two novel optically active alternating polymeric systems, poly(maleic anhydride-alt-octadecene) and poly(maleic anhydride-alt-2-methyl-2-butene), were functionalized with SP through an esterification process in a 1:1 monomer feed ratio, using pyridine as a catalyst. This methodology incorporated approximately 100% of the photoactive molecules into the main acrylic chain to prepare the alternating copolymers. These copolymers were characterized by UV-visible, FTIR, and 1H-NMR spectroscopy and analysis of their optical and thermal properties. When exposed to UV light, the photoactive polymer films can develop a deep blue color (566 nm in the absorption spectra). Finally, the study also assesses their capacity for photodynamic antimicrobial action in organic film. Notably, the photoactive P(MAn-alt-2MB)-PS significantly enhances the photodynamic antimicrobial activity of the photosensitizer Ru(bpy) against two bacterial strains of Staphylococcus aureus, reducing the minimum inhibitory concentration (MIC) from 2 µg/mL to 0.5 µg/mL. Therefore, 4 times less photosensitizer is required when mixed with the photoactive polymer to inhibit the growth of antibiotic-sensitive and -resistant bacteria. © 2025 by the authors.